(3eNJUQ CeKGd GdTQja GdeQJVis - (3eLO GdOjf CHh YHO Gddg eMeO Hf CMeO Hf YeQ GdMfaj GdCQHdjs; (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s ((3eMeO Hf eMeO Hf CMeO s)
(3ChdgG (B:s
(3aEfi hbaJ Ydi eLehY ef GdTYQ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
Keywords: (3GdCOHs